2019
DOI: 10.1002/jcb.29242
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metabolome changes in the HepG2 cells of apatinib treatment by using the NMR‐based metabolomics

Abstract: Neovascularization is required for the growth of tumors, vascular endothelial growth factor (VEGF) and related signal pathways are important in tumor angiogenesis. Apatinib is a highly selective and potent antiangiogenesis drug targeting the receptor of VEGFR2, blocking downstream signal transduction and inhibiting angiogenesis of tumor tissue. Apatinib has a wide range of antitumor activities in vitro and in vivo, but its effect on metabolic changes has not deeply research at present. Nowadays, our research f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The effect of using drugs of various natures was evaluated in 15 publications, [ 24 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Four publications studied the disturbance of the HepG2 metabolome after genetic editing [ 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of using drugs of various natures was evaluated in 15 publications, [ 24 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Four publications studied the disturbance of the HepG2 metabolome after genetic editing [ 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 56 articles, 4 had a direct link to raw data (from which one valuable dataset was kindly provided by the authors upon e-mail request [ 31 ], and three others deposited their data in a repository [ 27 , 46 , 68 ]). Twenty-three articles provided processed data in a reduced form (i.e., as complete lists of detected metabolites) [ 21 , 22 , 25 , 28 , 29 , 30 , 32 , 33 , 35 , 36 , 39 , 43 , 50 , 55 , 57 , 58 , 63 , 64 , 70 , 72 , 73 , 74 , 78 ]. The remaining 29 articles [ 23 , 24 , 37 , 38 , 40 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 56 , 59 , 60 , 61 , 62 , …”
Section: Resultsmentioning
confidence: 99%
“…The NMR‐based metabolomics was according to the methodology by Gu et al (2019). The dried substance was dissolved in D 2 O (0.5 mL) containing TMSP.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, researchers found that apatinib could also regulate the metabolic functions of liver cancer cells. For instance, Gu et al (25) reported that apatinib reduces the intake of pyruvate, and retards the secretion of lactate in HepG2 cells. According to Feng's study (26), apatinib has been demonstrated to enhance the synthesis of 3-hydroxybutyric acid (3HB), a metabolites inhibiting tumor growth both in vitro and in vivo, through activation of PPARa and promotion of fatty acid utilization.…”
Section: Metabolism Regulation Of Apatinib In Liver Cancermentioning
confidence: 99%